Kinematic Analysis of Geared Robotic Mechanism Using Matroid and T-T Graph Methods [Conference Object] - Amirinezhad, S. Vahid; Uyguroglu, Mustafa K.; Moghadam, Marzieh R. (IEEE, 2014)
In this paper, the kinematic structure of the geared robotic mechanism (GRM) is investigated with the aid of two different methods which are based on directed graphs and the methods are compared. One of the methods is Matroid Method developed by Talpasanu and the other method is TsaiTokad (T-T) Graph method developed by Uyguroglu and Demirel. It is shown that the kinematic structure of the geared robotic mechanism can be represented by directed graphs and angular velocity equations of the mechanisms can be systematically obtained from the graphs. The advantages and disadvantages of both methods are demonstrated relative to each other.
22nd Mediterranean Conference on Control and Automation (MED) -- JUN 16-19, 2014 -- Univ Palermo, Palermo, ITALY
Keywords: Geared Robotic Mechanism (GRM); Kinematic analysis; Matroid Method; T-T Graph Method